Investigation of the polymer-salt interactions in polymeric light emitting electrochemical cells: Electronic structure calculations and experimental studies - Galindo, Levy A. [UNESP]; Gozzi, Giovani [UNESP]; Fugikawa-Santos, Lucas [UNESP]; Faria, Roberto M.; Lavarda, Francisco C. [UNESP]; Batagin-Neto, Augusto [UNESP] (Elsevier, 2020)
Polymer light-emitting electrochemical cells (PLECs) are organic electronic devices which operating mechanism depends on the injection and transport of electronic charge carrier and the electrochemical doping of the organic semiconductor. The details of the interactions between the salt (or its ions) and the semiconducting polymer composing the device active layer provide important information about the electronic processes associated to the device operation in steady-state. In this context, the present paper proposes a study where theoretical results from Density Functional Theory (DFT) were obtained for three different steady-state operational regimes: i) without external voltage, in which the undissociated salt molecules interact with uncharged semiconducting polymer; ii) for applied voltages lower than the device turn-on (V<Eg/e), in which dissociated ions interact with uncharged semiconducting polymer; iii) for applied voltages higher than the turn-on (V>Eg/e), in which the dissociated ions interact with charged semiconducting polymer. In addition, the theoretical results have been confronted with experimental results of PLECs fabricated using different salt concentrations. For both theoretical and experimental approaches, we considered lithium triflate as the salt compound and poly[(9,9-dioctylfluorenyl-2,7-diyl)-co-(1,4-vinylenephenylene)] (F8PV) as the semiconducting polymer. We observed substantial changes in the electronic structure of the systems at the different operating regimes, which were interpreted in terms of the electronic charge injection from the electrodes and the electrochemical doping of the semiconducting polymer.
Keywords: Density functional theory; Electronic structure calculations; Fukui indexes; Light-Emitting Electrochemical Cells; Polymer-salt interation